Multiple supplementation and inclusion of passion fruit peel in the supplement, during the rearing of heifers in the dry season, in the state of Rondônia, Brazil (Research, Society and Development, 2022)
This study aimed at evaluating protein or protein-energy supplementation and the replacement of crushed corn by passion fruit peel in protein supplementation for growing heifers, during the dry season, in addition to the study of the economic viability of these supplements. The experimental design used was completely randomized, with 3 treatments and 8 repetitions. 24 heifers were used, divided into three lots: lot 1, protein supplementation based on core protein core and crushed corn (1:1), in the amount of 1 g kg-1 of body weight; lot 2, protein-energy supplementation, based on core protein and crushed corn (1:2), in the amount of 3 g kg-1 of body weight; and lot 3 protein supplementation, based on protein core and passion fruit peel (1:1), in the amount of 1 g kg-1 of body weight. The data were submitted to analysis of variance and the means compared by the Tukey test, at the level of 5%. The initial and final weights were similar for the supplements. The average daily weight gain was similar between the animals that received protein supplementation with crushed corn and the energy supplementation, and higher than the animals that received protein supplementation with passion fruit peel. Even with differences in weight gain, the daily profit per animal was similar. The weight gain of heifers in the rear is influenced by the type of supplementation, during the dry season, however the profitability can be similar.